Victims of Progress: Economic Integration, Specialization, and Wages for Unskilled Labor - Joseph Francois; Douglas R. Nelson (Tinbergen Institute, 2000)
In this paper we demonstrate that intra-industry trade (or FDI)between identical countries could produce theobserved deterioration in the relative wages of unskilled workers.This involves a model of North-Northintegration through either increased trade flows or increased MNE-based production. Our motivation in this regardis arguments to the effect that trade cannot be responsible for theobserved labour market trends because tradewith developing countries is quantitatively too small to havesignificant labour market effects. We also introduce arelatively unexploited class of model that possesses attractiveproperties with respect to the explicit incorporationof firm-theoretic considerations in trade models.
Keywords: F16; F15; J31; 330; trade and wages; trade and employment; FDI and wages; globalization and employment; Internationale Arbeitsteilung; Globalisierung; Intraindustrieller Handel; Lohnstruktur; Ungelernte Arbeitskräfte; Welt